Strategi Digital Fundraising dalam Peningkatan Zakat, Infaq, dan Shadaqah di Lazismu Jombang - Huda, Fatkur (Jurnal Ilmiah Ekonomi Islam, 2024)
The paradigm and environment of zakat management changed after the pandemic. This condition encourages zakat management organizations in Indonesia to do new and innovative things in zakat management, including the process of collecting, distributing, and utilizing zakat, as well as management structures. Conventional zakat collection methods will be replaced by digital methods that are easier, faster, and more transparent. More and more people in Indonesia are using the internet, making online donations easier nowadays. This research will provide scientific contributions as well as practical practices in the management of zakat donations. to find out the digital fundraising methods that Muhammadiyah Jombang has used to support zakat fundraising and to develop successful digital fundraising strategies. This study is qualitative research with a descriptive approach. In other words, the purpose of this study is to explain the method used by LazisMu Jombang to collect zakat funds from muzakis using a digital fundraising approach. The result is that the fundraising strategy used in raising zakat, infak, and shadaqah funds by LazisMu Jombang uses organic methods, namely Search Engine Optimization (SEO), Organic social media, Email office, WhatApp broadcast massage.